Higher Leptin-to-Adiponectin Ratio Strengthens the Association Between Body Measurements and Occurrence of Type 2 Diabetes Mellitus - Liao, Pei-Ju; Ting, Ming-Kuo; Wu, I-Wen; Chen, Shuo-Wei; Yang, Ning-I; Hsu, Kuang-Hung (Frontiers in Public Health, 2021)
Aims: This case–control study aimed to investigate the interrelations of body measurements and selected biomarkers on T2DM. Methods: We recruited 98 patients with T2DM and 98 controls during 2016–2018 in Taiwan. Body measurements were obtained using a three-dimensional body surface scanning system. Four biomarkers related to insulin resistance, adipokines, and inflammation were assayed. A multiple logistic regression model was used to perform multivariable analyses. Results: Four body measurements, namely waist circumference (odds ratio [OR] = 1.073; 95% confidence interval [CI] = 1.017–1.133), forearm circumference (OR = 1.227; 95% CI = 1.002–1.501), thigh circumference (OR = 0.841; 95% CI = 0.730–0.969), and calf circumference (OR = 1.250; 95% CI = 1.076–1.451), were significantly associated with T2DM. Leptin (OR = 1.090; 95% CI = 1.036–1.146) and adiponectin (OR = 0.982; 95% CI = 0.967–0.997) were significantly associated with T2DM. Six body measurement combinations, namely body mass index, waist-to-hip ratio, waist-to-height ratio, waist-to-thigh ratio, forearm-to-thigh ratio, and calf-to-thigh ratio (CTR), were significantly associated with T2DM. CTR had the strongest linear association with T2DM. Moderating effects of significant biomarkers, namely leptin and adiponectin, were observed. Participants with high leptin-to-adiponectin ratios and in the fourth CTR quartile were 162.20 times more prone to develop T2DM. Conclusions: We concluded that a combination of leptin and adiponectin modulated the strength of the association between body measurements and T2DM while providing clues for high-risk group identification and mechanistic conjectures of preventing T2DM.